IMPLEMENTATION OF NARCOTICS POLICY IN THE JURISDICTION OF THE TOMOHON POLICE RESORT - Andre Spencer Deeng; Goinpeace H. Tumbel; Devie S. R. Siwij (PT. Radja Intercontinental Publishing, 2026)
This study aims to describe, analyze, and explain the implementation of drug abuse policies in the Narcotics Criminal Investigation Unit of the Tomohon Police Resort Jurisdiction based on Law Number 35 of 2009 concerning Narcotics. The focus of the study covers three main indicators: (a) the adequacy and qualifications of Narcotics Unit personnel, (b) the adequacy and efficiency of operational budget allocation, and (c) the coverage and effectiveness of community-based prevention programs. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Research informants consist of the Head of the Narcotics Unit, members of the Narcotics Unit, and community leaders of Tomohon City. Data analysis uses the interactive model of Miles and Huberman, with data validity checks through source and technique triangulation. The research findings indicate that the implementation of narcotics policy at the Tomohon Police Department still faces various challenges. First, from a personnel perspective, there is a gap between ideal and actual needs, with only about 69 percent of personnel being met. Furthermore, there is uneven distribution of specialized training certification due to limited Education and Training (Dikbang) and Latnis (National Training and Development) quotas. Second, from a budget perspective, the allocation for outreach programs is only about 10-15 percent, without any real-world needs analysis support. There is no efficiency measurement mechanism, and there is still a reliance on the National Narcotics Agency (BNNP) for in-depth forensic analysis. Third, from a prevention program perspective, coverage remains limited, with the Drug-Free Village program limited to only one sub-district. Outreach methods are dominated by one-way, less interactive lectures, and there is no systematic rehabilitation referral mechanism. This study recommends additional personnel, expansion of prevention programs, development of digital-based outreach methods, and an increase in the budget allocated for preventive activities.